Effects of Non-invasive Brain Stimulation on Multiple System Atrophy: A Systematic Review - Zhang, Mengjie; He, Ting; Wang, Quan (Frontiers in Neuroscience, 2021)
Background/objective: Multiple system atrophy (MSA) refers to a progressive neurodegenerative disease characterized by autonomic dysfunction, parkinsonism, cerebellar ataxia, as well as cognitive deficits. Non-invasive brain stimulation (NIBS) has recently served as a therapeutic technique for MSA by personalized stimulation. The primary aim of this systematic review is to assess the effects of NIBS on two subtypes of MSA: parkinsonian-type MSA (MSA-P) and cerebellar-type MSA (MSA-C). Methods: A literature search for English articles was conducted from PubMed, Embase, Web of Science, Cochrane Library, CINAHL, and PsycINFO up to August 2021. Original articles investigating the therapeutics application of NIBS in MSA were screened and analyzed by two independent reviewers. Moreover, a customized form was adopted to extract data, and the quality of articles was assessed based on the PEDro scale for clinical articles. Results: On the whole, nine articles were included, i.e., five for repetitive transcranial magnetic stimulation (rTMS), two for transcranial direct current stimulation (tDCS), one for paired associative stimulation, with 123 patients recruited. The mentioned articles comprised three randomized controlled trials, two controlled trials, two non-controlled trials, and two case reports which assessed NIBS effects on motor function, cognitive function, and brain modulatory effects. The majority of articles demonstrated significant motor symptoms improvement and increased cerebellar activation in the short term after active rTMS. Furthermore, short-term and long-term effects on improvement of motor performance were significant for tDCS. As opposed to the mentioned, no significant change of motor cortical excitability was reported after PAS. Conclusion: NIBS can serve as a useful neurorehabilitation strategy to improve motor and cognitive function in MSA-P and MSA-C patients. However, further high-quality articles are required to examine the underlying mechanisms and standardized protocol of rTMS as well as its long-term effect. Furthermore, the effects of other NIBS subtypes on MSA still need further investigation.